2014
DOI: 10.3892/ol.2014.2594
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lapatinib monotherapy on occult breast cancer presenting with cutaneous metastases: A case report

Abstract: The case of a 72-year-old female who identified a lymph node enlargement in the left axilla is reported in the present study. A lymph node biopsy revealed a metastatic adenocarcinoma of the axillary lymph node. Following various assessments, the patient was diagnosed with occult breast cancer and lymph node metastases, for which treatment was initiated. Trastuzumab monotherapy was administered as the patient was elderly, positive for the hepatitis B virus and exhibited the following immunostaining/immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In breast cancer patients the decision for chemotherapy versus aromatase inhibitors is dependent on tumor phenotype. For HER2 + breast cancer patients, trastuzumab, ado‐trastuzumab emtansine, and lapatinib have demonstrated to be effective in reducing cutaneous lesions in several case reports 51–53 . Patients with ER + disease are better suited for aromatase inhibitors, either as the initial treatment or as maintenance therapy following disease control by other systemic and local therapies 56–60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer patients the decision for chemotherapy versus aromatase inhibitors is dependent on tumor phenotype. For HER2 + breast cancer patients, trastuzumab, ado‐trastuzumab emtansine, and lapatinib have demonstrated to be effective in reducing cutaneous lesions in several case reports 51–53 . Patients with ER + disease are better suited for aromatase inhibitors, either as the initial treatment or as maintenance therapy following disease control by other systemic and local therapies 56–60 …”
Section: Discussionmentioning
confidence: 99%
“…After 2 years of recurring cutaneous metastases, she was started on nab-paclitaxel and trastuzumab, which led to the complete resolution of her skin lesions. 52 Noguchi et al 53 reported on a patient whose HER2 + cutaneous metastases resolved after switching from trastuzumab to lapatinib and remained lesion free by the end of the study's 34-month follow-up period. Pizzuti et al 54 Eribulin was studied in one observational study, which cited the drug's demonstrated safety in Phases II and III clinical trials for locally advanced and metastatic breast cancer.…”
Section: Chemotherapymentioning
confidence: 99%
“…Several cases of cutaneous metastases after or during treatment have been defined in the literature [11,12]. Herein a case is described in which a patient with Her-2-positive metastatic breast cancer had zosteriform cutaneous progression 7 years later treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that anti-HER2 mAbs may not be effective in mediating an effective therapeutic effect in the cutaneous metastases of HER2-positive BC. There have been reports of some cases of cutaneous progression during or after treatment with anti-HER2 mAbs (11)(12)(13)(14). Pyrotinib is an oral, irreversible pan-ErbB receptor tyrosine kinase inhibitor (TKI), which has anti-epidermal growth factor receptor (EGFR)/HER1, HER2, and HER4 activity (15).…”
Section: Introductionmentioning
confidence: 99%